Pharmacokinetic and pharmacodynamic study of LFA3Ig fusion protein in healthy volunteers and patients with psoriasis - Li Xian-ping; Li Jing; Yan Heng; Hou Sheng; Qian Wei-zhu; Chen Yong-chuan; Tang Min; Li Bo-hua; Zhang Da-peng; Zhou Bo; Wang Hao; Hao Fei; et al. (Acta Pharmacologica Sinica, 2016)
Aim: To evaluate the pharmacokinetics (PK) and pharmacodynamics of the LFA3Ig fusion protein (LFA3IgFP) in healthy volunteers and patients with chronic plaque psoriasis. Methods: The clinical trials included 2 phase I open studies. Study 1 was an open-label dose escalation study in 24 healthy volunteers, and study 2 was a single-group, open-label study in 12 patients with chronic plaque psoriasis. The serum drug concentrations were measured, and the concentration-time data were analyzed by compartmental analysis using the Practical Pharmacokinetic Program. Results: In study 1, after intramuscular (im) administration at a dosage of 5, 15, and 25 mg, the concentration-time curves of LFA3IgFP fitted well to a 1 compartment open model. Areas under the concentration-time curves increased linearly with dose. Clearance rates (Cls F) and elimination half-lives (T1/2ke) had no significant difference between different dose groups. A transient, slight decline of CD4+ and CD8+ T-cell subsets was observed after administration. In study 2, after im administration at a dosage of 15 mg weekly for 8 weeks, the concentration-time curve was best fitted to a 1 compartment open model, with a T1/2ke of 307.9±32.7 h. The steady state was attained after the fifth administration. Conclusion: The PK behaviors of LFA3IgFP in healthy volunteers and patients with chronic plaque psoriasis complied with linear kinetics within the examined dose range. A significant accumulation was observed after repeated administration at a dose of 15 mg weekly for 8 weeks.